From Celluloid to Cyberspace The Media Arts and the Changing Arts World - McCarthy, Kevin F. (RAND Corporation, 2002)
Current knowledge of the operation of the arts world and its underlying dynamics is limited, especially with regard to the media arts--art that is produced using or combining film, video, and computers. The authors examine the organizational features of the media arts, placing them in the context of the broader arts environment and identifying the major challenges they face. They take a structural point of view, discussing audiences, media artists as a group, arts organizations, and funding for the media arts.